COVID-19-related fear, stress and depression in school principals: impacts of symptoms like COVID-19, information confusion, health-related activity limitations, working hours, sense of coherence and health literacy. (31st December 2022) - Duong, Tuyen Van; Nguyen, Minh H.; Lai, Chih-Feng; Chen, Sheng-Chih; Dadaczynski, Kevin; Okan, Orkan; Lin, Cheng-Yu
Abstract: Background: School principals have been reported to have a higher prevalence of burnout and psychological problems than their colleagues. During the pandemic, extra workload and pressure from unprecedented situations potentially cause fear, stress and depression. Therefore, we aimed to explore associated factors of stress, fear of COVID-19 (F-CoV-19S) and depressive symptoms among school principals. Methods: A cross-sectional online survey was conducted in Taiwan from 23 June to 16 July 2021. Data of 413 school principals were collected, including socio-demographic factors, COVID-19-related factors, work-related information, health status, sense of coherence (SoC), health literacy (HL), F-CoV-19S, stress and depression. Multiple linear and logistic regression models were utilized to explore associations. Results: School principals with symptoms like COVID-19 (S-COVID-19-S), or with health-related activity limitations had a higher score of stress ( B  = 0.92; p  = .039) ( B  = 1.52; p  < .001) and a higher depression likelihood (OR = 3.38; p  < .001) (OR = 3.06; p  < .001), whereas those with a better SoC had a lower stress score (B = −1.39; p  < .001) and a lower depression likelihood (OR = 0.76; p  = .020). School principals confusing about COVID-19-related information had a higher score of stress ( B  = 2.47; p  < .001) and fear ( B  = 3.77; p  < .001). The longer working time was associated with a higher fear score ( B  = 1.69; p  = .006). Additionally, school principals with a higher HL score had a lower stress score (B = −1.76; p  < .001), a lower fear score (B = −1.85; p  < .001) and a lower depression likelihood (OR = 0.53; p  = .043). Conclusions: Health-related activity limitations, S-COVID-19-S, COVID-19-related information confusion and longer working hours were positively associated with at least one mental health problem (e.g. stress, fear and depression), whereas better SoC and HL showed the benefits to mitigate fear, stress and depressive symptoms in school principals. Our study provides evidence for appropriate strategies to improve principals' mental health during the pandemic. Key messages: School principals with health-related activity limitations or with symptoms like COVID-19 were more likely to be stressed and depressed. Higher levels of stress and fear were observed in school principals who confused about COVID-19-related information, and who had longer working time than before the pandemic. Better sense of coherence and higher health literacy could potentially mitigate the fear, stress and depressive symptoms in school principals.